Characterization of functional domains of the cblD (MMADHC) gene product. Issue 5 (11th April 2014) - Jusufi, Jehona; Suormala, Terttu; Burda, Patricie; Fowler, Brian; Froese, D. Sean; Baumgartner, Matthias R.
Abstract: In humans vitamin B12 (cobalamin, Cbl) must be converted into two coenzyme forms, methylcobalamin (MeCbl) and adenosylcobalamin (AdoCbl), in order to maintain intracellular homeostasis of homocysteine and methylmalonic acid, respectively. Previously we have shown that in cblD patients three types of MMADHC mutations exist: 1) null mutations N‐terminal to Met116 cause isolated methylmalonic aciduria ( cblD ‐MMA) due to AdoCbl deficiency; 2) null mutations across the C–terminus (p.Y140‐R250) cause combined methylmalonic aciduria and homocystinuria ( cblD ‐MMA/HC) due to AdoCbl and MeCbl deficiency; 3) missense mutations in a conserved C‐terminal region (p.D246‐L259) cause isolated homocystinuria ( cblD ‐HC) due to MeCbl deficiency. To better understand the domain boundaries related to MeCbl formation, we made selected point mutations and C‐terminal truncations in MMADHC and tested rescue of MeCbl and AdoCbl synthesis in immortalized cblD ‐MMA/HC patient fibroblasts. Testing 20 mutations (15 missense and five C‐terminal truncations) across p.P154‐S287 revealed the presence of a region (p.R197‐D226) responsible for MeCbl synthesis, which gave a similar cellular phenotype as cblD ‐HC. Further, mutation of the polypeptide stretch between the new and patient defined regions (p.D226‐D246) and directly C‐terminal to the patient region (p.L259‐R266), gave cellular phenotypes intermediate to those of cblD ‐HC and cblD ‐MMA/HC. Finally, C‐terminal truncation of more than 20 amino acids resulted in a cblD‐MMA/HC like cellular phenotype, while truncation of between ten and 20 amino acids resulted in a cblD‐HC like cellular phenotype. These data suggest that specific regions of MMADHC are involved in differential regulation of AdoCbl and MeCbl synthesis and help better define the boundaries of these regions.